Regulation of chronic neuroinflammation through dietary herbal products - Bhat, Kumar M. R.; Upadhya, Raghavendra; Adiga, Shripathi; Kumar, S. E. Praveen; Manjula, S. D.; Acharya, Nanda; Subramanian, Hari H.; Upadhya, Dinesh (Frontiers in Nutrition, 2025)
Chronic neuroinflammation is a consequence of disease pathogenesis underlying neurological disorders at large. While the immune response that triggers inflammatory signaling cascades is unresolved, its progression could cause functional damage to neurons and glial cells, including astrocytes, microglia, and oligodendrocytes. Controlling neuroinflammatory signaling at the early stage of disease pathogenesis is critical to prevent irreversible tissue necrosis. While the application of anti-inflammatory drugs is standard practice, their protracted use is known to cause gastrointestinal injuries, further enhancing the risk of cardiovascular, renal, liver, and lung diseases. Several medicinal herbs and herbal products with anti-inflammatory potential could be effective substitutes. This review aims to identify the preclinical data from important dietary herbal products that have demonstrated anti-neuroinflammatory efficacy in several animal models. The reviewed dietary herbal products are sourced from Bacopa monnieri, Centella asiatica, Emblica officinalis, Piper nigrum, Zingiber officinale, Punica granatum, Mucuna pruriens, Clitoria ternatea, Moringa oleifera, Phoenix dactylifera and Curcuma longa. This review is based on emphatic data from these products demonstrating the significant anti-neuro-inflammatory potential that could probably reduce neuroinflammatory signaling in a neurological disorder and promote brain health and well-being. Abundant scientific evidence shows that critical proinflammatory cytokines in the brain, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-six (IL-6), could be controlled through regular consumption of such dietary herbal products without debilitating side effects for their disease-modifying impacts.